Comparative study of left and right dermatoglyphic palm pattern prints on individual reflective personality - Choy, Benjamin Kai Ghit (2015)
There exists a close relation between the health condition of an individual and the dermatoglyphic patterns of the palms in the realm of medical diagnosis [1]. Much information is actually within the covert structure of a palm print. Since the ancient times, traditional Chinese medicine (TCM) has found that the palm print is linked to heath and character; and with extensive research, linkage is made to nationality, geographival distribution, temperament, intelligence, et cetra [2]. In addition, the use of palm prints is presented with an entertainment value of fortune telling and predicting into one’s future, and also in areas of personal identification, and criminology. However, there is a paucity of research conducted to affirm the accuracy of palm prints as an indicator of individual characteristics. This project aims to understand the relation between the similarity of left and right dermatoglyphic palm patterns and individual reflective personality. The technique of image recognition and processing of the region of interest (ROI) is used to obtain the line edge map for analysis and comparison. The greater the number of lines and secondary creases is associated with one’s cognitive and psychological demeanour. The greater the difference in lines present on the left and right palms translates to an increased in the mental and emotional complexity of an individual. This might be indicative how one communicates, and herein proving the postulate that people with higher dissimilarity in their palm prints tend to be complicated or inaccurate in the way they think and speak. Therefore, a software was developed and adopted to calculate the similarity between the left and right palm prints. The result was then compared to the threshod of the training data set, which was taken and refined from the image database of Hong Kong Polytechnic University. Individuals that form the training data set as well as the test subjects vary in gender, age, race, and nationality, thus providing good sampling of the entire population. As this project only assessed specific personality traits, it serves as a rudimentary guide for future works and further development.